ETNOTEOLOGI DIGITAL DAN AREOPAGUS MODERN: KAJIAN KISAH PARA RASUL 17:22-28 - Febriaman Lalaziduhu Harefa; Aris Elisa Tembay (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
This study is motivated by the gap between the massive dynamics of digital transformation and the church’s mission practices, which have not yet fully integrated local culture into the digital sphere in a theologically reflective manner. Although Acts 17:22-28 demonstrates how Paul utilized Greek cultural symbols at the Areopagus as a starting point for proclaiming the Gospel, scholarly exploration of the application of this principle within the framework of digital ethnotheology remains relatively limited. Therefore, this study aims to analyze the concept of digital ethnotheology as a model for integrating local culture in the development of contextual mission in the digital era, based on an exegetical reflection on Acts 17:22-28.The method employed is qualitative research with a descriptive-analytical approach through a literature review of contextual theology, missiology, and cultural digitalization. The findings indicate that digital space can be understood as a “modern Areopagus,” providing strategic opportunities for the church to communicate the Gospel through narratives, symbols, art, music, and ritual expressions rooted in local culture. The discussion affirms that the Gospel does not abolish culture but transforms it, while also highlighting theological challenges such as the potential for syncretism and the hegemony of digital globalization.